Genres of Popular Culture and Their Aesthetic Value - Tasevska Hadji Boshkova, Iskra (Institute of Macedonian Literature, 2016)
In this postmodern epoch, it is an indubitable fact that genre criticism has broadened its perspective. Since questions risen concern not only generic form, but also the coincidence between the aesthetic range of literary work of art, genre, and popular culture, the proposed article wishes to examine the crucial problem – What is the beauty of popular culture/literature? And yet another question: What are the historical grounds of popular literature? Ever since Plato and Aristotle, forms of mimesis (as a certain modes of enunciation, containing specific subject matter) have always been analyzed throughout their beauty and truthfulness. Aristotle gave rise to the “aesthetic” difference between tragedy and comedy, and the other forms of representation. This stratification in the period of classicism was known as difference between high (noble), middle and low (simple) genres. If we accept the argument of the theory of literary reception, we can point out to the questions in a different direction – What are the decisive conditions that determine writer’s choice of particular genre? Is everything acceptable from artistic point of view? This rumination leads us back to the nature of aesthetics and its mixed nature (since the beginnings) that consists of the verisimilar and the artistic (Longinus’ poetic fantasy). We propose a general view of one specific genre in Macedonian popular culture, i.e. column in historical perspective, starting from one of the exclusive genres in the 19-century Macedonian literature – sermon (discourse). In this context, we underline the specific nature of pseudo-fictional columns (narratives) of Macedonian professor and writer Venko Andonovski, whose venture is to combine the factual and the fictional in order to examine the grounds and possibilities of literary conventions.
Keywords: genre criticism, aesthetics, column, pseudo-factual, pseudo-fictional.